Hepatitis B, С, D prevalence among childbearing age women in Ha Giang province, Vietnam: a cross-sectional study - Evgeniia Lichnaia; Nga Bui Thi Thanh; Olga Petrova; Daria Starkova; Nhai Tran Thi; Cuong Vo Viet; Alexander Dmitriev; Olga Kalinina (International Journal of Infectious Diseases, 2025)
Background/Aim: The high mortality rates from liver cancer caused by hepatitis B virus (HBV) and hepatitis C virus (HCV) occur in Asia and Africa. In HBV endemic countries (HBsAg prevalence > 8%), mother-to-child transmission of HBV plays an important role in the epidemiology of the infection. Almost 33% of all infected children become infected in pregnancy and 50% become infected during childbirth. The goal of this study was to evaluate the prevalence of HBV, HCV, HDV in childbearing age women in the rural province Ha Giang. Material and Methods: A total of 661 women of 18-49 years old (mean age 34.9±8.5) belonging to different ethnic minorities were enrolled in the study conducted in several district of the Ha Giang province in 2019-2023. Of 661 women, 51.1% (338/661) were Hmong ethnic, 22.6% (149/661) were Tay ethnic, 13.0% (86/661) were Dao ethnic, and 13.3% (88/661) were belonged to other small minorities. The specific serological markers of HBV, HCV, HDV were detected by ELISA using commercial kits (RPC Diagnostic Systems, Russia). Results: Totally, the prevalence of HBsAg, anti-HBc and anti-HBs was 10.7% (71/661; 95%CI 8.6-13.3), 55.2% (365/661; 95%CI 51.4-59.0), 36.6% (242/661; 95%CI 33.0-40.4), respectively. DNA HBV was detected in 9.4% (62/661; 95%CI 7.4-11.8). The prevalence of HCV antibodies was 0.8% (5/661; 95%CI 0.3-1.8). HCV RNA was detected in 0.5% (3/661; 95%CI 0.2-1.3). No specific serological markers to HDV were found in all studied samples. Among the participants, only 38.9% (255/661; 95% CI 34.9-42.3) women were negative for markers to viral hepatitis B, C and D. Conclusion: The obtained results indicate a high level of HBV prevalence among childbearing age women living in the northern rural province Ha Giang in Vietnam. Screening program of women of childbearing age in endemic counties of Asia and Africa is still very important to reveal woman with high risk of perinatal transmission of viral hepatitis B, C and D at the pregravid period to prevent perinatal transmission to child.